Long‐term outcome of immunologic autograft engineering. Issue 2 (24th February 2022) - Porrata, Luis F.; Inwards, David J.; Ansell, Stephen M.; Micallef, Ivana N.; Johnston, Patrick B.; Villasboas, Jose C.; Paludo, Jonas; Markovic, Svetomir N.
Abstract: Our phase III trial reported that autograft‐absolute lymphocyte count (A‐ALC) improved survival post‐autologous peripheral blood hematopoietic stem cell transplantation (APBHSCT) for a short‐term follow‐up of 2 years. We evaluated retrospectively in our phase III trial patients that the A‐ALC still confers survival benefit with a longer follow‐up. With a median follow‐up of 127.6 months, patients infused with an A‐ALC ≥ 0.5 × 10 9 cells/kg experienced better overall survival (HR = 0.392, 95% confidence of interval [CI]: 0.224–0.687, p < 0.001) and progression‐free survival (HR = 0.413, 95% CI: 0.253–0.677), p < 0.0004). This study supports that A‐ALC provides long‐term survival benefit post APBHSCT.